Impact of Early Gadget Use on Development in Children Aged 1-3 Years in Asmorobangun Village, Puncu District, Kediri Regency: Penggunaan Gadget Dini pada Anak Usia 1-3 Tahun terhadap Perkembangan di Desa Asmorobangun Kecamatan Puncu Kabupaten Kediri - Nuraisya, Wahyu; Kondo, Lenia Murni (JURNAL KEBIDANAN, 2024)
The development of the times requires a person to introducing gadgets from an early age. Children become less social and communicate with other people. This causes children to receive the right stimulus less than optimally, resulting in delays in aspects of motor development and child socialization. The aim of this research is to analyze the relationship between early gadget use in children aged 1-3 years. This type of research is analytic correlation uses the method crossectional. Variable independent This research is the use of gadgets and variables dependent child development. The research was carried out on May 13-26 2024 at Posyandu Asmorobangun Village. Population of 98 respondents using simple random sampling technique obtained a sample of 79 respondents. The research used the KPSP questionnaire. used the Spearman rho statistical test. Results showed that the category of gadget use was in the moderate category with doubtful child development as many as 21 (26.6%), the results, it showed a value of (p=0.000) This shows that (p<0,05) which shows that there is a relationship between early gadget use and the development of children aged 1-3 years. Use of gadgets with high intensity in early childhood can have various kinds of impacts or negative influences on the individual's physical and psychological well-being on the child's development, including gross motor skills, fine motor skills, language, as well as socialization and independence.